Effect of Hydrogen on Plastic Strain Localization of Construction Steels; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Barannikova S. A. Svetlana A.; Lunev A. G. Alexey Gennadievich; Nadezhkin M. V. Mikhail Vladimirovich; Zuev L. B. Lev B. (2014, 2014)
Title screen